Ceramic papers containing Y zeolite for toluene removal - Cecchini, Juan Pablo (2011)
A papermaking technique with a dual polyelectrolyte retention system was used for the preparation of NaY zeolite-containing papers, which implied the use of cationic and anionic polymers. Two kinds of fibers were employed, either cellulosic or ceramic ones, and accordingly papers with different characteristics were obtained: those that only contained cellulosic fibers for low temperature applications, cellulosic papers, and those prepared using both cellulosic and ceramic fibers - ceramic papers - for high temperature applications. Although a decrease in their mechanical properties due to calcination was observed, zeolitic ceramic papers resulted easy to handle for practical applications. Zeolite was quantified through BET surface area measurements. SEM images indicated a good dispersion of zeolite particles within the cellulosic paper whereas in the ceramic paper they appeared anchored on ceramic fibers. The zeolitic papers prepared resulted efficient as toluene sorbents, the adsorption capacities of zeolitic ceramic papers being higher than those of zeolitic cellulosic papers. In the case of zeolitic cellulosic papers, the amounts of released toluene were lower than those of adsorbed toluene, implying that the treatment up to 160 °C did not completely eliminate the hydrocarbon. Also, TPD profiles showed that toluene is chemically retained up to high temperatures (ca. 420 °C) in zeolitic ceramic papers. Toluene adsorption values demonstrate that zeolite dispersed into the cellulose/ceramic matrix is as effective as powder massive zeolite in retaining the hydrocarbon, which highlights the potential application of these zeolitic structures as sorbent materials both for low and high temperatures.